2014
DOI: 10.1292/jvms.13-0433
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Susceptibility of <i>Malassezia pachydermatis</i> Isolates from Canine Skin with Atopic Dermatitis to Ketoconazole and Itraconazole in East Asia

Abstract: Topical or oral azole antifungals are commonly used in canine atopic dermatitis (AD), as the lipophilic yeast Malassezia pachydermatis exacerbates canine AD. To examine whether canine AD lesions harbor azole-resistant M. pachydermatis isolates in East Asia, we investigated the in vitro susceptibility of M. pachydermatis isolates to ketoconazole (KTZ) and itraconazole (ITZ) obtained from AD lesions of canines in Japan, Korea and Taiwan. The minimum inhibitory concentrations (MICs) of KTZ and ITZ were measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 9 publications
2
35
0
Order By: Relevance
“…In the supernatant of M furfur culture, the presence of the remaining cytokines was not detected at all, or their concentration was very low. The highest concentration of cytokines was found in the supernatant from the cultures of M pachydermatis, which can be the possible reason for the greater severity of the inflammatory reaction in the course of M pachydermatis infection in animals in comparison to symptoms that appear in humans . Another study conducted by Baroni et al in 2001 showed that keratinocytes stimulated by M furfur produced decreased amounts of IL1α and increased amounts of IL‐10 and TGF‐β1, leading to an inhibition of IL‐6 and TNFα.…”
Section: Pathogenetic Mechanism Of Lesions Caused By Malassezia In Pamentioning
confidence: 98%
“…In the supernatant of M furfur culture, the presence of the remaining cytokines was not detected at all, or their concentration was very low. The highest concentration of cytokines was found in the supernatant from the cultures of M pachydermatis, which can be the possible reason for the greater severity of the inflammatory reaction in the course of M pachydermatis infection in animals in comparison to symptoms that appear in humans . Another study conducted by Baroni et al in 2001 showed that keratinocytes stimulated by M furfur produced decreased amounts of IL1α and increased amounts of IL‐10 and TGF‐β1, leading to an inhibition of IL‐6 and TNFα.…”
Section: Pathogenetic Mechanism Of Lesions Caused By Malassezia In Pamentioning
confidence: 98%
“…In recent years, have been described some strains of M. pachydermatis resistant in vitro to azoles, Malassezia pachydermatis is recognised as an exacerbating factor of canine atopic dermatitis. Watanabe et al suggested that in these cases, the resistance of these yeast to azoles could be the cause of mutations and overexpression of genes that could be favoured by oral treatment with azole of long time.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, have been described some strains of M. pachydermatis resistant in vitro to azoles, Malassezia pachydermatis is recognised as an exacerbating factor of canine atopic dermatitis. Watanabe et al suggested that in these cases, the resistance of these yeast to azoles could be the cause of mutations and overexpression of genes that could be favoured by oral treatment with azole of long time. At the same time, Álvarez‐Pérez et al think that the interpretive breakpoints for antifungal susceptibility testing of Malassezia species are not yet available, which means that any classification of isolates into susceptible, intermediate and resistant categories remains speculative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there are concerns regarding the evolution of Malassezia drug resistance. Some in vitro studies have reported that Malassezia from lesions in dogs with atopic dermatitis were less susceptible to, or even resistant to, azole antifungals as compared to Malassezia taken from clinically asymptomatic dogs . This was especially evident in strains producing biofilms .…”
Section: Introductionmentioning
confidence: 99%